1Influence of graphene oxide additive on the tribological and electrochemical corrosion properties of a PEO coating prepared on AZ31 magnesium alloy. (June 2020) - Zhang, Yulin; Chen, Fei; Zhang, You; Du, Cuiwei
Abstract: Graphene oxide (GO) was incorporated into a plasma electrolytic oxidation (PEO)-based coating to further promote the tribological properties and corrosion resistance of AZ31 Mg alloys. The results demonstrated that the embedded GO additives reduced the surface roughness and porosity, promoted the formation of blocked pores and minor-sized structures, and enhanced the microhardness of the GO-containing coatings. The composite coating prepared with 20 mL L −1 GO additive was sufficient for sustaining a low and stable friction coefficient and high wear endurance. In addition, the inclusion of a GO additive in the composite coating could effectively decrease the corrosion rate and enhance the polarization resistance. Highlights: A GO-containing coating was fabricated on AZ31 magnesium alloy via plasma electrolytic oxidation. The composite coating was sufficient for sustaining a low, stable friction coefficient and high wear endurance. The GO additivescould effectively decrease the corrosion rate and increase the polarization resistance.